Prevalence of hypomineralised second primary molars (HSPM): A systematic review and meta-analysis. - O'Connell, Anne; Oleg?rio da Costa, Isabel (My University, 2022)
Aim: To evaluate the prevalence of HSPM worldwide on a child and a tooth level and investigate the influence of diagnostic criteria on the prevalence of HSPM. Design: A comprehensive literature search was performed through MEDLINE/PubMed, Scopus, and Web of Science databases. The grey literature was also screened as were the reference lists of included studies. An adaptation of the Newcastle-Ottawa Scale was used to evaluate the quality of the studies. A meta-analysis was performed to determine the pooled prevalence of HSPM. Results: The search strategy identified 1,988 articles, 487 were retrieved for full-text evaluation, and 37 studies were included in the meta-analysis (32 for child and 23 for tooth level prevalence), providing data from 26,805 individuals and 81,107 molars. The prevalence of HSPM was 6.8% (95% CI 4.98%-8.86%) on a child level and 4.08% on a tooth level (95% CI = 2.80%-5.59%). The diagnostic criteria used did not seem to influence the prevalence results (P > .05). The majority of the papers (75%) showed a low-to-moderate risk of bias. Conclusion: There was a broad variation in the prevalence reported that may be attributed to differences in the study population. The present meta-analysis showed a HSPM prevalence worldwide of 6.8% on a child level and 4.1% on a tooth level.
PUBLISHED
Keywords: Children; Hypomineralised second primary molars; Meta-analysis; Prevalence; Systematic review; DEVELOPMENTAL DENTAL DEFECTS; PAEDIATRIC DENTISTRY; Children